Metabolisable energy of grass and red clover silages fed to sheep at maintenance level. (29th April 2020) - Krizsan, S. J.; Pang, D.; Fatehi, F.; Rinne, M.; Huhtanen, P.
Abstract : This study investigated the effect of forage type (grass or red clover) and harvesting time (primary growth or regrowth) of silage on energy and N utilisation by sheep fed at maintenance level. Specifically, the assumption of constant loss of energy of digestible organic matter from energy losses in urine and CH4 applied in evaluation of silage metabolisable energy (ME ) was investigated. Urinary excretion of high-energy phenolic compounds related to solubilisation of lignin was assumed to affect urinary energy (UE ) losses from sheep fed highly digestible grass silage (GS ). A total of 25 primary growth and regrowth silages of timothy ( Phleum pratense ) and meadow fescue ( Festuca pratensis ) grass mixtures and red clover ( Trifolium pratense ) samples collected in digestibility trials with sheep, including faecal and urine samples, were used for energy and N determinations. Urinary concentration of monophenolic compounds and CH4 emissions in vitro were also analysed. Daily faecal N output, CH4 yield (MJ/kg DM intake), proportion of CH4 energy in digestible energy (DE ) and proportion of UE in DE were greater ( P ≤ 0.03) in sheep fed red clover silage (RCS ) than GS. Furthermore, less ( P = 0.01) energy was lost as UE of DE in sheep fed primary growth GS compared with the other treatments. The relationship between UE and silage N intake or urinary N output for both silage types (i.e. grass v . red clover) was strong, but the fit of the regressions was better for GS than RCS. The CH4 /DE ratio decreased ( P < 0.05) and the UE/DE ratio increased ( P < 0.05) with increasing organic matter digestibility in RCS. These relationships were not significant ( P < 0.05) for the GS diets. The regression coefficient was higher ( P < 0.05) for GS than RCS when regressing ME concentration on digestible organic matter. The results of this study imply that ME/DE ratio is not constant across first-cut GS of different maturities. The ME production response may be smaller from highly digestible first-cut GS but could not be clearly related to urinary excretion of monophenols derived from solubilisation of lignin. Furthermore, energy lost in urine was not clearly defined for RCS and was much more predictable for GS from silage N concentration.